Recognizing sentimental emotions in text by using Machine Learning - Bushra, Tabassum Khan; Saha, Kallol; Mulki, Ammin Hossain; Khan, Sanjana Sabah; Binta Amzad, Afrin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.